Продление ресурса промышленных и отопительных котлов от 12 МВт котельных и ТЭЦ - Сигал, И.Я.; Смихула, А.В.; Марасин, А.В.; Лавренцов, Е.М. (Энерготехнологии и ресурсосбережение, 2015)
Показано, что имеется техническая возможность при небольших капитальных затратах модернизировать существующие в Украине промышленные и отопительные котлы мощностью от 12 МВт, отработавшие заводской ресурс, для доведения их технико-экономических и экологических показателей до современного мирового уровня c продлением их ресурса на 15–20 лет. Показано, що є технічна можливість при невеликих капітальних витратах модернізувати існуючі в Україні промислові та опалювальні котли потужністю від 12 МВт, які відпрацювали заводський ресурс, для доведення їх техніко-економічних та екологічних показників до сучасного світового рівня з продовженням їх ресурсу на 15–20 років. In Ukraine there is the technical possibility low-cost modernization of existing industrial and heating boilers, which capacity from 12 MW and they achieved the expiration date, with increasing duration of operation for 15–20 years and bringing their technical, economic and environmental performance to the modern world’s level. When the boiler house operates at nominal capacity, and has significant residual duration of operation, it is necessary to include the following activities: the increase of surface heating of boilers to achieve modern efficiency; the application of various methods of reducing emissions of NOx. When boiler operating in less than 2/3 of peak power of the nominal capacity should: the decrease value of the nominal capacity of boilers to economically expedient in view of the exhaust gases temperature; the creation of exhaust gases recirculation in boilers using existing draught-blowing equipment. In both cases it is necessary replace the burner on improved one with low NOx emissions